Temporal hierarchy of cortical responses reflects core-belt-parabelt organization of auditory cortex in musicians - Benner, Jan; Reinhardt, Julia; Christiner, Markus; Wengenroth, Martina; Stippich, Christoph; Schneider, Peter; Blatow, Maria (Cerebral cortex, 2023)
Abstract - Human auditory cortex (AC) organization resembles the core-belt-parabelt organization in nonhuman primates. Previous studies assessed mostly spatial characteristics; however, temporal aspects were little considered so far. We employed co-registration of functional magnetic resonance imaging (fMRI) and magnetoencephalography (MEG) in musicians with and without absolute pitch (AP) to achieve spatial and temporal segregation of human auditory responses. First, individual fMRI activations induced by complex harmonic tones were consistently identified in four distinct regions-of-interest within AC, namely in medial Heschl’s gyrus (HG), lateral HG, anterior superior temporal gyrus (STG), and planum temporale (PT). Second, we analyzed the temporal dynamics of individual MEG responses at the location of corresponding fMRI activations. In the AP group, the auditory evoked P2 onset occurred ~25 ms earlier in the right as compared with the left PT and ~15 ms earlier in the right as compared with the left anterior STG. This effect was consistent at the individual level and correlated with AP proficiency. Based on the combined application of MEG and fMRI measurements, we were able for the first time to demonstrate a characteristic temporal hierarchy (“chronotopy”) of human auditory regions in relation to specific auditory abilities, reflecting the prediction for serial processing from nonhuman studies.
Online veröffentlicht: 14. Februar 2023
Gesehen am 18.03.2025